Relationships between care burden, resilience, and depressive symptoms among the main family caregivers of stroke patients: A cross-sectional study - Fang, Linlin; Dong, Mengyuan; Fang, Wenbo; Zheng, Jin (Frontiers in Psychiatry, 2022)
Abstract Background: Although studies indicate that resilience is related to care burden, and depressive symptoms, the underlying mechanism between those variables remains unknown. Thus, the present study aimed to explore the potential mediating role of resilience between care burden and depressive symptoms in family caregivers of patients with stroke. Methods: A cross-sectional study was conducted with a convenience sample of 245 main family caregivers of stroke patients recruited from the neurology department of Tertiary A hospital of China. The PROCESS macro (model 4) was conducted to explore the relationships between care burden, resilience, and depressive symptoms. Results: The results showed that: when controlling the side of hemiplegia, the Barthel Index score, education level, monthly income, care time per day and living with patients in regression equations, resilience partially mediated the relationship between care burden and depressive symptoms with the mediation effect ratio of 26.32%. Conclusions: The findings indicated the protective effect of resilience in alleviating the negative influence of care burden on depressive symptoms, suggesting that resilience-training intervention may be developed to mitigate depressive symptoms among the main family caregivers of stroke patients.